2021
DOI: 10.5826/dpc.1104a91
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Skin: An Overview of Mind Body Therapies as a Treatment Strategy in Dermatology

Abstract: Stress has multiple and wide-ranging physiologic and clinical impacts on skin disease. This has led to an interest in mind body therapies as potential adjunct treatments for skin disease. The stress response results in the activation of the endocrine, neurologic, and immune systems, with a resulting cascade of impacts, that are both systemic and cutaneous. The 2 main arms of the stress response are the sympathetic nervous system and the hypothalamic-pituitary-adrenal axis. The resultant release of cortisol, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Reduction of stress improves the atopic symptoms, and mind–body therapies, such as PMR and acupuncture, have been highlighted as adjunctive therapies [ 36 ]. In a study of PMR in AD, EASI scores and stress markers were reported to improve [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of stress improves the atopic symptoms, and mind–body therapies, such as PMR and acupuncture, have been highlighted as adjunctive therapies [ 36 ]. In a study of PMR in AD, EASI scores and stress markers were reported to improve [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Holistic care incorporating complementary and alternative medicine with a low risk profile, for example, yoga, the use of chiropractic and osteopathic practices, meditation and massage therapy, is increasingly being used as an adjunct to conventional medicine to address biological, psychological and psychosocial factors 11 . Although randomized controlled trials (RCT) are limited, holistic approaches may have beneficial effects on the skin disorder, pruritus and pain, as well as on anxiety, stress, and sleep disorders to improve patients' well‐being 10 . Furthermore, treatment adherence may be improved if both the psychiatric disorder and dermatological disorder are managed in everyday dermatologic practice 12 …”
Section: Implications For Patient Carementioning
confidence: 99%
“… 168 Further evidence suggests that the peripheral HPA axis in the skin also plays a vital role in the etiopathogenesis of CU via inflammatory and neurotransmission disturbances. 153 , 164 , 169 Mast cells and epidermal and hair follicle keratinocytes are effector cells in this axis expressing CRH receptor 1 (R1) receptors and produce CRH and IL-18 in response to stress. 170 The neuroendocrine, behavioral, and autonomic responses to stress are all orchestrated by CRH-R1, whereas IL-18 contributes to severe cutaneous inflammation.…”
Section: Chronic Urticariamentioning
confidence: 99%